Pulsating Auroral Forms and Their Association with Geomagnetic Giant Pulsations - Taylor, Michael J.; Chisham, G.; Orr, D. (Planetary and Space Science, 1989)
On the night of 29/30 October 1987 a giant pulsation (Pg) was recorded on the EISCAT magnetometer cross and the U.K. Sub-Auroral Magnetometer Network (SAMNET), accompanied by a variation in auroral luminosity with an identical periodicity of 77 s. Coincident all-sky image data showed that the auroral emissions arose from a series of pulsating patches (which exhibited lifetimes of the order 5–15 s) whose occurrence was modulated with a 77 s periodicity. At several times during this event, a new type of pulsating auroral patch was observed. These data provide a unique example of the auroral precipitation signature during a Pg event.